Implementation of P2P nodes detection based on decision tree - Yong-ping DONG; Xiang-zhan YU; Gang WU (Tongxin xuebao)
A P2P nodes detection method based on decision model was proposed by a long time of observation.As this method is a statistical analysis of the transport layer packet characteristics,identification of the network node for encrypted or unencrypted P2P applications is effective.Experiment shows that this method has higher accuracy and lower false positive rate and false negative rate.